Black Soldier Fly: Nutrition Source of Layer Hen Raising - Lokaewmanee, Kanda (Journal of Vocational Education in Agriculture, 2024)
It’s successful and produces outstanding outcomes to raise laying chickens. Must rely on academic expertise from choosing breeds of good-laying chickens include proper house management and a market for the produced goods. But high-quality feed is essential. Presently, costly egg-laying feed expenses are a common issue for poultry producers that raise eggs. Consequently, in order for farmers to lower the cost of feed. Thus, it’s intriguing to consider usingblack soldier flyas a feed source for hens that lay eggs. The high nutritional content of black soldier fly includes protein, lipids, amino acids, and fatty acids that are good for the growth and egg production of laying hens. Most black soldier fly usage patterns concentrate on using the larvae in both fresh and dried forms. Based on the data gathered, it was discovered that the black soldier fly larvae stage is the most widely used for rearing laying hens. As a result, the egg production can reach 97–98% at the point where 10–20% of the soybean meal in diet is replaced. There are differences in the amounts and ways that black soldier flies are used as laying hen nutrition. Thus, more research on the ratios, consumption trends, and price of raising laying hens is required.